Learning together: Teaching, relationships, and teachers' work. Issue 137 (15th April 2013) - Bernstein‐Yamashiro, Beth; Noam, Gil G.
Abstract: Teachers find that having close personal relationships with students is deeply rewarding in their work and that they contribute to more effective classrooms. The relationships, which many consider to be part and parcel of good teaching, afford teachers the opportunity to reach students intellectually and emotionally. Still, the relationships can be overwhelming and confusing for teachers. In interviews, teachers at a large and a small high school discuss how the relationships offer them both rewards and challenges in their work, their personal lives, and their efforts to humanize their classrooms.